2005
DOI: 10.1186/1475-2891-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Food selection associated with sense of coherence in adults

Abstract: BackgroundFavorable dietary habits promote health, whereas unfavorable habits link to various chronic diseases. An individual's "sense of coherence" (SOC) is reported to correlate with prevalence of some diseases to which dietary habits are linked. However, understanding what determines an individual's dietary preferences and how to change his/her behavior remains limited. The aim of the present study was to evaluate associations between dietary intake and SOC in adults.MethodsDiet intake was recorded by an 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
67
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 21 publications
19
67
0
9
Order By: Relevance
“…SOC may influence the aetiology of, and recovery from disease through effective coping, by avoiding behaviours that are directly detrimental to health such as smoking, excessive drinking, unhealthy diet or sedentary lifestyle, and by adopting behaviours that can reduce the severity of illness, such as seeking treatment early or compliance to it [Antonovsky, 1996]. Indeed, prior research in adults has shown that a strong SOC is related to more favourable dental behaviours [Savolainen et al, 2004;Lindmark et al, 2005;Savolainen et al, 2005;Bernabé et al, 2009a;Savolainen et al, 2009;Lindmark et al, 2011b]. Longitudinal studies may help to examine this novel research area in greater depth.…”
mentioning
confidence: 99%
“…SOC may influence the aetiology of, and recovery from disease through effective coping, by avoiding behaviours that are directly detrimental to health such as smoking, excessive drinking, unhealthy diet or sedentary lifestyle, and by adopting behaviours that can reduce the severity of illness, such as seeking treatment early or compliance to it [Antonovsky, 1996]. Indeed, prior research in adults has shown that a strong SOC is related to more favourable dental behaviours [Savolainen et al, 2004;Lindmark et al, 2005;Savolainen et al, 2005;Bernabé et al, 2009a;Savolainen et al, 2009;Lindmark et al, 2011b]. Longitudinal studies may help to examine this novel research area in greater depth.…”
mentioning
confidence: 99%
“…Dietas variadas e fracionadas estão associadas ao aporte adequado de macro e micronutrientes 24,25 . Os indivíduos mais conscientes do seu comportamento alimentar são, na maioria das vezes, aqueles que buscam maiores informações sobre saúde e alimentação, e tal percepção e conhecimento se refletem nas suas escolhas e atitudes alimentares, levando-os ao consumo adequado de FVL [26][27][28][29] .…”
Section: Discussionunclassified
“…Even in food selection, both men and women with high SOC scores reported more healthy food choices than those with lower scores 28) . Unhealthy behaviors might lead to poorer subjective well-being.…”
Section: Discussionmentioning
confidence: 99%